Evaluation of Turkish emergency medicine physicians’ knowledge on emergency management of tooth avulsion - Raziye Kuru; Gülsüm Duruk (European Oral Research)
Purpose: Tooth avulsion is a type of trauma that requires emergency intervention, and a significant number of patients apply to the emergency. The aim of this study is to evaluate the level of knowledge and the awareness about tooth avulsion among emergency medicine physicians throughout Turkey. Materials and Methods: The study was conducted with 545 physicians, working in emergency departments. An online questionnaire about tooth avulsion was applied to the participants. The questionnaire consisted of 3-section which evaluated personal information, the level of knowledge of avulsion cases in primary and permanent dentition, and the level of training on this subject. Results: Of the physicians, 61.3% had not previously received education on dentoalveolar traumas, 58.7% would replant an avulsed permanent tooth, 28.3% would prefer replantation to be performed “immediately”, and 28% would prefer milk as the ideal storage medium. The mean±SD and median(min-max) values of the correct answer scores on a scale of 0 to 35 were 16.42±7.08 and 17(0-32), respectively. 45.6% of the physicians’ level of knowledge was below the median score. Conclusion: The level of knowledge about tooth avulsion among Turkish emergency medicine physicians is not sufficient and there is a need to improve the knowledge level of physicians with comprehensive educational programs. This study indicates that the training of the physicians about the subject will reflect positively on the treatment of dental trauma patients.